Questionnaire data on visual, perceptual, and emotional characteristics of Japanese adults - Imaizumi, Shu (Data Brief, 2019)
The dataset comprises 344 Japanese adults’ responses to validated psychological scales to assess the following: (1) visual function and its relation to quality of life, (2) susceptibility to visual discomfort, such as aversion to stimuli and eyestrain, (3) hypersensitivity and hyposensitivity across sensory modalities, (4) positive and negative moods, and (5) proneness and sensitivity to disgust. The dataset also includes participants’ gender, age, response times, and dates of participation. The dataset might be used for exploratory analyses and cross-cultural studies.